An Analysis of the Impact of New Autonomous Weapons on the Israel - Palestine Conflict - Fiona Namutosi (Uganda Christian University, 2025)
This dissertation critically examines the impact of autonomous weapons system within the context of the Israel-Palestine war, exploring both the strategic implications and the profound ethical, legal, and humanitarian concerns they raise. As the nature of modern warfare evolves with rapid advances in artificial intelligence and robotics, autonomous weapons have emerged as powerful tools capable of reshaping conflict dynamics, reducing the need for direct human involvement while simultaneously complicating questions of accountability and proportionality. Through an interdisciplinary research approach, this study analyzes how AWS have been deployed, tested, and potentially deployed in Israe;-Palestine context, assessing their influence on military strategy, civilian safety, and International Humanitarian Law. Drawing on case studies, expert interviews, and legal frameworks, the research explores the blurred lines between defense and aggression, and the moral consequences of delegating lethal decisions to machine. Ultimately, this work contends that while AWS offer certain technical advantages, their integration into asymmetric conflicts such as Israel-Palestine risks exacerbating civilian harm, deepening power imbalances, and undermining mechanisms of accountability. The study calls for urgent international discourse and regulation to address the ethical vacuum surrounding autonomous warfare, especially in protracted conflicts marked by historical grievances and contested narratives.
THESIS